The legal status of persons with mental disabilities in Bulgaria - Boyuklieva, Iliana (Law Journal of New Bulgarian University, 2022)
The article discusses some problems of the Bulgarian legislation related to legal status of persons with mental disabilities. The national legislation regarding legal status of persons with mental disabilities is considered, outlining the problems of their legal capacity, legal incapacitation and fundamental rights. In this context, it compares the national legal framework with the Convention on the Rights of Persons with Disabilities. In conclusion, legal reform is needed to regulate in detail the legal status of these individuals in sync with international principles.